PKM PEMANFAATAN BAHASA DAN DIGITAL MARKETING BAGI KOMUNITAS WIRAUSAHA RAJUTAN HMPS PRODI PBSI UNIVERSITAS MUHAMMADIYAH BUTON - Nadir La Djamudi; Asrul Nazar; Tofan Stofiana; Susiati Susiati; Marwa Marwa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Language and digital marketing have an important and effective role to introduce to choose and buy products. Apart from being able to reach a wider audience, digital marketing makes it easier for potential customers to order and/or buy products. Language in promotions can also affect the perceptions and impressions of potential consumers. Service partners (knitting students) are aware of the role of language and digital marketing as promotional tools to increase turnover. Some social media and digital marketing have been used as promotional tools by partners (knitting students). It is hoped that the assistance provided by the PkM Team will continue and be developed both in terms of language and digital marketing. It is also hoped that this service activity can inspire other business units and introduce HMPS PBSI products or SMEs more broadly, nationally and even internationally.